2015
DOI: 10.5130/ajceb.v15i1.4214
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Payment Problems in the New Zealand Construction Industry

Abstract: Payment delays and losses persist in the construction industry and continue to be a key concern to industry practitioners. Therefore an exploration of the key causes of payment delays and losses is undertaken in this study with the ultimate objective of seeking mitigating solutions. The study adopted a survey approach using an online questionnaire, administered to practitioners from the New Zealand construction industry, comprising consultants, head contractors and subcontractors. The data obtained was analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…Payment is known as the lifeblood of a project, and it is vital for all parties involved in the construction industry. As mentioned by Judi et al [2], payment defaults in the Malaysian construction industry have relatively , 0 (2019) MATEC Web of Conferences https://doi.org/10.1051/matecconf/2019 I 2018 increased in number in recent years, and it has come into existence since the year 2000 [1]. The researchers further argued that some Malaysian contractors who are registered with CIDB Malaysia have experienced late payments and non-payment issues, either in governmentfunded projects or private-funded projects.…”
Section: Payment Defaultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Payment is known as the lifeblood of a project, and it is vital for all parties involved in the construction industry. As mentioned by Judi et al [2], payment defaults in the Malaysian construction industry have relatively , 0 (2019) MATEC Web of Conferences https://doi.org/10.1051/matecconf/2019 I 2018 increased in number in recent years, and it has come into existence since the year 2000 [1]. The researchers further argued that some Malaysian contractors who are registered with CIDB Malaysia have experienced late payments and non-payment issues, either in governmentfunded projects or private-funded projects.…”
Section: Payment Defaultsmentioning
confidence: 99%
“…As payment is said to be the lifeblood of the construction industry, payment disputes remain a major problem among construction players. Ramachandra and Rotimi [1] revealed that payment is the main subject matter of construction disputes which result in project delays, reduced profitability, and abandoned projects. Payment problems are still the main issue among construction players, more so payment from the client to the main contractor, either in the form of advance payment, progress payment or final payment [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the possible solutions according to contractors are the right to regular periodic payment, the right to a defined time frame for payment, the right to a speedy dispute resolution mechanism e.g. : adjudication, the right to interest due to payment delay, the mandatory creation of a trust account for retention sums, payment bonds, a right to suspend work, the restriction of the right to set-off or withhold sums due, the creation of a right to a lien, the prohibition of pay when paid clauses in contracts (Munaaim, Danuri, Abdul and Hanid, 2006;Ramachandra and Rotimi, 2015). However, some of the solutions have side effects such as suspension of work as explained in previous comments and thus this study is very important to be conducted.…”
Section: Strategies Used By Road Contractors To Deal With Payment Delaysmentioning
confidence: 99%
“…Payment problems in the construction industry are not a new phenomenon. Such problems have been widely recognized for more than four decades by prior research (Wu, 2010;Rahman and Ye, 2010;Wu, Kumaraswamy and Soo, 2011;Ramachandra and Rotimi, 2015). Due to payment delays to contractors who executed government construction projects, contractors have either abandoned projects or implemented the projects at a very slow pace (Daniel, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted, this is due to poor cost planning activities that have been the main practice in the construction industry since time in memorial, thus, the recession in 2007 strongly affected the industry. It was reported in China that late and eventual non-payments along with lack of security caused substantial cash flow difficulties leading to risks of insolvency of construction parties [36,45]. There have been several studies which have indicated that cost planning practices are not effective thus cost overruns and delayed payment are perceived to be identical to the construction industry [46,12].…”
Section: Introductionmentioning
confidence: 99%